TGFβ3 Regulates Periderm Removal Through ΔNp63 in the Developing Palate. Issue 6 (June 2015) - Hu, Lihua; Liu, Jingpeng; Li, Zhi; Ozturk, Ferhat; Gurumurthy, Channabasavaiah; Romano, Rose‐Anne; Sinha, Satrajit; Nawshad, Ali
<x xml:space="preserve">Abstract</x> The periderm is a flat layer of epithelium created during embryonic development. During palatogenesis, the periderm forms a protective layer against premature adhesion of the oral epithelia, including the palate. However, the periderm must be removed in order for the medial edge epithelia (MEE) to properly adhere and form a palatal seam. Improper periderm removal results in a cleft palate. Although the timing of transforming growth factor β3 (TGFβ3) expression in the MEE coincides with periderm degeneration, its role in periderm desquamation is not known. Interestingly, murine models of knockout (−/−) TGFβ3, interferon regulatory factor 6 (IRF6) (−/−), and truncated p63 (ΔNp63) (−/−) are born with palatal clefts because of failure of the palatal shelves to adhere, suggesting that these genes regulate palatal epithelial differentiation. However, despite having similar phenotypes in null mouse models, no studies have analyzed the possible association between the TGFβ3 signaling cascade and the IRF6/ΔNp63 genes during palate development. Recent studies indicate that regulation of ΔNp63, which depends on IRF6, facilitates epithelial differentiation. We performed biochemical analysis, gene activity and protein expression assays with palatal sections of TGFβ3 (−/−), ΔNp63 (−/−), and wild‐type (WT) embryos, and primary MEE cells from WT palates to analyze the association between TGFβ3 and IRF6/ΔNp63. Our results suggest that periderm degeneration depends on functional TGFβ3 signaling to repress ΔNp63, thereby coordinating periderm desquamation. Cleft palate occurs in TGFβ3 (−/−) because of inadequate periderm removal that impedes palatal seam formation, while cleft palate occurs in ΔNp63 (−/−) palates because of premature fusion. J. Cell. Physiol. 230: 1212–1225, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company